US Trade Policy: Plus Ça Change - Glauber, Joseph W. (American Enterprise Institute, 2023)
Key Points: As a presidential candidate, Joe Biden promised to reverse Donald Trump’s unilateral approach to trade policy, but two and a half years into his presidency, Biden has changed little of his predecessor’s trade regime, instead pursuing a “polite protectionism” that emphasizes social and environmental responsibility. A historical net exporter of agricultural products, the US has generally benefited from a system that recent presidential administrations have undermined by imposing tariffs on trading partners and blocking appointment to the Appellate Body of the World Trade Organization. The Biden administration should make good on its promises to reverse Trump’s protectionism, thereby expanding access to foreign markets for US agricultural producers.